Implementasi Refleksi Pembelajaran Dalam Proses Pelatihan Di Balai Diklat Keagamaan Surabaya - ., Mushollin (Balai Diklat Keagamaan Surabaya, 2022)
Learning reflection is an important part in the learning and training stages. Reflection on learning will provide more